Has Carbon Disclosure Become More Transparent in the Global Logistics Industry? An Investigation of Corporate Carbon Disclosure Strategies Between 2010 and 2015 - David M. Herold (Logistics)
Global logistics companies are increasingly disclosing carbon related information due to institutional and stakeholder pressures. Existing research, however, is limited to categorizing these pressures and their influences on corporate carbon disclosure strategies. In particular, literature to date has not distinguished between different carbon disclosure strategies and how they may have changed over time. In response, this paper: (1) proposes a framework that depicts four different carbon disclosure responses and strategies based on internal and external pressures; and (2) subsequently analyzes and compares corporate carbon disclosure strategies between 2010 and 2015. Using a sample of 39 leading global logistics companies, carbon disclosure strategies are categorized based on the analysis of 25 applied carbon management practices from Bloomberg ESG to see if carbon management practices and the associated strategies have changed. The findings show overall shifts to more transparent corporate carbon disclosure strategies between 2010 and 2015 with an increase of applied carbon management practices in both internal and external actions.